ANALYSE DE LA PRECISION ET DE LA QUALITE DES DONNEES DE VACCINATION DE ROUTINE DANS LA ZONE DE SANTE DE MANONO, PROVINCE DE TANGANYIKA, RD Congo. - LOBWA B., Santhos; Salomon OTOWANGE MANDEFU; Xavier BOGENDA BAILA; Dieudonné EPELEKA MAZEMBE (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
The precision and the quality of the data returned by the sanitary formations remained our preoccupation of the whole time. It is to this title that we gave ourselves like to owe to size up the degree of precision and the qualitative elements in relation with the data of routine vaccination returned by the Zone of health of MANONO the first nine months of the year 2018. It is about the vaccination data in the Pentavalent 3 and to the Vaccine against the Rougeole(VAR) for our survey. For that to make, we had to consider the data of 27 areas of health that this Zone of health counts during the active period of January to September 2019. We pursued like objective the assessment of the precision and the quality of the routine vaccination data in the Zone of health of Manono ; precisely: To determine the complétude and the promptness of routine vaccination reports and to value the accurateness of rapportage. This with the help of the DQS tools, precisely two indicators of which the factor of verification and the indication of quality. Of the analysis of the data of this health Zone, we noted that the indications of quality of the routine vaccination data in the BCZS and of 66% and 70% were respectively at the Centers of health., therefore <80%. Brief, the quality poses problem again. We have in more noted a rapportage out norms of most areas of health (70%), presenting either one on, or either again one coins - rapportage of the data produced. Let’s keep all the same that the complétude (100%) and the promptness (99,6%) were two major assets to preserve for the Zone of health of MANONO.